Portal Hypertensive Polyposis in Advanced Liver Cirrhosis: The Unknown Entity? - David Kara; Anna Hüsing-Kabar; Hartmut Schmidt; Inga Grünewald; Gursimran Chandhok; Miriam Maschmeier; Iyad Kabar (Canadian Journal of Gastroenterology and Hepatology)
Background. Portal hypertension is a serious complication of liver cirrhosis. Objective. To identify relevant endoscopic findings in patients with advanced cirrhosis and consecutive portal hypertension. Methods. This was a retrospective study of liver transplant candidates who underwent upper gastrointestinal endoscopy between April 2011 and November 2015. Results. A total of 1,045 upper endoscopies were analyzed. Portal hypertensive gastric and duodenal polyps were frequently observed and were associated with thrombocytopenia (p = 0.040; OR: 2.4, 95% CI 1.04–5.50), Child-Pugh score > 6 (p = 0.033; OR: 2.3, 95% CI 1.07–4.92), Model for End Stage Liver Disease score > 16 (p = 0.030; OR: 4.1, 95% CI 1.14–15.00), and previous rubber band ligation (p < 0.001; OR = 5.2, 95% CI 2.5–10.7). These polyps often recurred after polypectomy; however, no malignant transformation occurred during the observational time until October 2017. The most common endoscopic finding was esophageal varices, observed in more than 90% of patients. Conclusion. Portal hypertensive polyposis is common in patients with advanced cirrhosis. Our data suggest that these polyps have benign characteristics.